2012
DOI: 10.3892/or.2012.1655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of the adrenomedullin gene on the growth and chemosensitivity of ovarian cancer cells

Abstract: Abstract. Adrenomedullin (AM), a potent vasodilator peptide, is present in various types of tumors. Here, we constructed short hairpin RNA (shRNA) in order to target the AM gene in vitro using RNA interference (RNAi) technology. HO8910 ovarian cancer cells were transfected, and the effects of AM on proliferation and chemosensitivity of the cells were examined. RT-PCR, real-time PCR and western blot analysis were performed to detect the AM gene and protein expression. The MTT assay was used to observe the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The ADM-specific short hairpin RNA (shRNA) and no-science shRNA were designed and constructed in our previously study [25]. The oligonucleotide shRNAs based on the small interfering RNA (siRNA) sequences were cloned into pRNA-U6.1/Neo (GeneScript, Piscataway, NJ, USA), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The ADM-specific short hairpin RNA (shRNA) and no-science shRNA were designed and constructed in our previously study [25]. The oligonucleotide shRNAs based on the small interfering RNA (siRNA) sequences were cloned into pRNA-U6.1/Neo (GeneScript, Piscataway, NJ, USA), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Tumour cell lines evaluated included small cell lung carcinomas, non-small cell lung carcinomas, breast, nervous system (glioblastoma, neuroblastomas), ovarian, prostate, adrenal, chondrosarcoma, and chronic monocytic leukemia [ 166 ]. These data have been replicated on different tumour cell lines such as pancreatic cell lines (PANC1, L3.6, HPAFII, SU86.86) [ 110 , 116 , 169 ], gliomas [ 170 , 171 ], prostate cancer cell lines [ 162 , 172 175 ], ovarian cancer [ 149 , 176 , 177 ], osteosarcoma [ 109 ], renal carcinoma [ 121 , 178 ], multiple myeloma [ 179 ], bladder urothelial cell carcinoma [ 120 ], pituitary adenomas [ 145 ], colorectal cancer [ 119 , 147 , 148 ], breast cancer [ 144 ], endometrial cancer [ 38 ], hepatocellular carcinoma [ 132 ] and others.…”
Section: Introductionmentioning
confidence: 87%
“…As noted above, the presence of AM peptide, as well as AM receptors, has been described in ovarian cancer cells [ 178 ]. Silencing of the AM gene inhibited the proliferation and increased the chemosensitivity of HO8910 cells by downregulation of Bcl-2 and p-ERK, as described for other cancer cell types [ 176 ]. However, other authors have reported that AM effect in ovarian cancer cells is weak as revealed by proliferation assays and cell cycle analysis performed under stressing conditions, such as serum starvation and/or hypoxia [ 149 ].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our previous study, we had constructed short hairpin RNA (shRNA) targeting ADM gene in vitro 31. The oligonucleotide shRNA based on the small interfering (siRNA) sequences were cloned into pRNA-U6.1/Neo (GeneScript, Piscataway, NJ, USA), named pRNA-shADM.…”
Section: Methodsmentioning
confidence: 99%